Evaluation of Settlement Land Suitability Based on Remote Sensing and Geographical Information Systems in The City of Ambon - Lasaiba, Mohammad Amin (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2023)
The increasing need for settlement land has led to different suitability-based uses. This study evaluates land suitability for settlement, limiting factors, and development priorities. The methods used is qualitative with spatial analysis and quantitative with grading based on land units. This study uses Landsat 8 OLI/TIRS data, SRTM DEM, administrative maps, soil types, lithology, and landforms. Data was analyzed based on satellite imagery, approximations, and overlays. The study results show that processing satellite imagery with reasonable accuracy. For land suitability for settlements, the very unsuitable class is dominated by an area of 23592.48 acres, while the very suitable place is 6033.39 acres. For the direction of settlement development, priority I covers an area of 3,181.34 acres, priority II covers an area of 2,852.05 acres, and priority III covers an area of 8,237.89 acres. The findings in this study can be seen in the development of settlements in the regions that are not suitable (D2 II Pm), covering an area of 204.19 acres. Therefore, local governments need to apply regional regulations strictly to create land sustainability and prevent any impacts that may arise.